CHILD PERSONALITY AND VIOLENCE PREVENTION: PROSOCIAL BEHAVIOR PROFILE - Briceño, Efrain Duarte; Chan, Jorge Carlos Aguayo; Pinto Loria, María de Lourdes; Rosado Che, Gabriel Jesús (IJRDO- Journal of Educational Research, 2017)
The present study aimed to develop a child's personality profile of prosocial behavior, as well as the profile development by sex. The study was of cross-sectional and descriptive type with a non-probabilistic sample. Six instruments were used: BAS 3 by Silva and Martorell (2001 ); Prosocial behavior questionnaire for parents and teachers by Weir and Duveen (1981); Scale criminal anti-social behavior by Seisdedos (2001); CABS by Wood, Michelson and Flynn (1978); Scale of Self Concept by Flores, Cortés, Estrada and Campos (2012) and EIS by Garaigordobil (2000). The participants were 89 6th grade students from two conurbated public schools of Merida, Yucatan. The brute data were transformed to z grades in order to obtain a  normal score distribution with a mean value M = 0. The study results indicate that the prosocial personality profile of the sample is low; regarding gender, it was found that female participants behaved more prosocially than males.